Use of Preventable Risk Integrated Model on behavioral risk factors: a scoping review and bibliometric analysis - Castillo-Paredes, Antonio; Ferrari, Gerson (Frontiers in Nutrition, 2025)
IntroductionBehavioral or habit-based risk factors lead to the development of non-communicable diseases, causing early deaths, disability due to these diseases, and high economic burdens on the public or private health system. The use of the Preventable Risk Integrated Model through the creation of counterfactual scenarios could simulate in the future the number of deaths that can be delayed or prevented if one or more risk factors associated with diet, tobacco, alcohol, or physical activity are modified.ObjectiveThe objective of this research was to explore the scientific evidence available on the use of the Preventable Risk Integrated Model, identifying the main findings, the most productive authors on the subject, the most used keywords, the countries of origin of the research, and the scientific journals where these studies are published.MethodsThrough the development of four research questions, a search strategy was established for the development of the scoping review and bibliometric analysis of the information obtained.ResultsA total of 24 articles were identified that used the Preventable Risk Integrated Model, which were available in their titles and research abstracts. Regarding the results obtained, this model was used on topics related to food consumption, food composition, nutrient intake, and prevention of non-communicable diseases by reducing some nutrients related to sodium or saturated fats, in addition to the creation of new models supported by the Preventable Risk Integrated Model. In addition, the authors who research the topic, the use of keywords, the countries that have done the most research on the subject, and indexed journals were identified.DiscussionThe studies analyzed focus on recommendations proposed by non-governmental organizations and national policies of each country, while other studies focus on the areas of reduction of death, reduction of costs associated with the prevention of non-communicable diseases and other studies provide information on the creation of the model and another related to the use in other behavioral habits. In addition, networks are visualized for the follow-up of authors doing research on the use of this model.ConclusionFinally, the use of the model allowed the projection of preventable deaths or those that could be delayed when modifying the risk factors that cause non-communicable diseases; however, caution must be taken in its proper use due to the consultation of various sources such as databases, use of national surveys, or international information repositories.Systematic Review RegistrationIdentifier: DOI 10.17605/OSF.IO/WYNHJ.